Da xenofobia ao racismo: mal-estar moderno - Koltai, Caterina (Percurso, 2013)
Realização: Ana Claudia Patitucci, Bela M. Sister, Cristina Parada Franch, Danielle Melanie Breyton, Deborah Joan de Cardoso e Silvio Hotimsky